Vaccination Coverage and Attitudes in Children and Adults on Biologic Therapies: Cocooning Strategies, Undervaccination Factors and Predictors of Favorable Attitudes - Charikleia Kariniotaki; George Bertsias; Emmanouil Galanakis; Chrysoula Perdikogianni (Vaccines)
Background: Infections pose a significant risk of morbidity and mortality to patients on biologics, with the vaccination of both patients and their close contacts serving as a key preventive measure. Despite its importance, there are limited data on the vaccination coverage for this group, and no studies have examined the vaccination status of patients’ close contacts. Objectives: To assess vaccination rates among patients on biologics and their household contacts, identifying reasons for inadequate vaccination and examining factors influencing vaccination status and attitudes is crucial. Methods: A cross-sectional study was conducted from September 2022 to February 2023 at the two hospitals in Heraklion, Crete, including adult and pediatric patients on biologics. Data were collected through medical records and interviews and analyzed using Microsoft Excel 2016 and MedCalc2006. Results: Among the 446 adults, vaccination rates were as follows: 83% for COVID-19, 73.8% for influenza, 64.5% for the pneumococcal conjugate vaccine, 29.6% for the pneumococcal polysaccharide vaccine, and 4% for Tdap. Among the 26 children included, those with basic immunization schedule coverage exceeded 96%, but rates for the vaccines usually administered at adolescence were lower (Tdap: 47.8%, HPV: 42.1%, MenACWY: 66.7%). COVID-19 vaccination was at 38.5%. Regarding the additional vaccines recommended due to treatment-induced immunosuppression, 69.2% of pediatric patients received the annual influenza vaccine, while only 19.2% received the pneumococcal polysaccharide vaccine. Household contacts demonstrated low vaccination rates (<59%), except for COVID-19 (81%). Female gender (p < 0.007) and older age (by 1 year, p < 0.001) were associated with favorable attitudes and higher coverage in adults, while in pediatric patients, no statistically significant associations were found. A lack of physician recommendation was the primary reported reason for not being vaccinated. Conclusions: Significant vaccination gaps exist among patients on biologics and their close contacts, largely due to inadequate physician recommendations. Raising awareness and strengthening healthcare provider roles are essential to improve coverage in this high-risk group.